Procurement Training in Modern Socio-Economic Conditions - DEGTEV, Gennady Valentinovich; GLADILINA, Irina Petrovna; SERGEEVA, Svetlana Alexandrovna; KURDAKOV, Anton Vladimirovich; SULOEVA, Anastasia Alekseevna (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).10, 2018)
Procurement training is one of the most important personnel tasks of each country. This is due to the growing importance of public procurement in modern socio-economic conditions. The international personnel training experience in the field of procurement shows the high importance of the improvement of procurement training methods. The comparative analysis of foreign and domestic procurement training practices makes it possible to define the key aspects of the improvement of the training methods for not merely post-graduate students, but also for advanced training and professional retraining students.